عيادات العيون الالكترونية حجز ،إرشاد ، تشخيص - مناصرة, سوسن; دباس, تسنيم; مرقطن, أسماء (Palestine Polytechnic University , department of information technology)
Eye health and vision care are the most important things that considered to any human being, no one can imagine himself without seeing for a day . So, it is very important to track and trace problems in the early stages so that we can overcome them. In light of the technological development in which we live we have to search for a way to take advantage of this development to bring attention to eye health and preserving it is easy and available for all. Our project aims to make a site that enables people to check on their eyes by conducting several tests and consult doctors and read tips that are posted on the site. Through this website people can examine their seeing and communicate with the doctor, they are able to choose a particular doctor using the Search icon and communicate with him to follow up his case. The patient receives instructions about taking care of eye health and how to deal with certain diseases, and to benefit from a project that already prepared a book of appointments electronically "Doctor.ps" be booked, so the patient can choose a doctor and then review his appointments and book the suitable time. The system will automatically send a notification to the patient in case of cancelling the appointment or being changed by a doctor. Also through the website the patient can communicate with his doctor, and book a suitable appointment .The site has been programmed by using the PHP language and used the STMP transport codes for sending and receiving. الملخص: تعتبر صحة العيون ورعاية النظر هما اكثر الامور أهمية لدى أي إنسان ، فلا أحد يستطيع أن يتخيل نفسه يوماً واحداً بلا بصر. لذا من المهم جداً تعقب وتتبع المشاكل في مراحل مبكرة لكي نتمكن من التغلب عليها. و في ظل التطور التكنولوجي الذي نعيشه قمنا بالبحث عن وسيلة تستغل هذا التطور لجعل الاهتمام بصحة العيون والمحافظه عليها أمر سهل و متاح للجميع . مشروعنا يهدف إلى موقع يمكِّن الأشخاص من الاطمئنان على أعينهم عن طريق إجراء عدة فحوصات واستشارة الأطباء وقراءة النصائح التي يتم نشرها على الموقع . ومن خلال هذا الموقع يستطيع الأشخاص فحص نظرهم والتواصل مع الطبيب، حيث يتم اختيار طبيب معين باستخدام أيقونة البحث والتواصل معه لمتابعة حالته. ويتلقي المريض الإرشادات حول الإهتمام بصحة العيون وكيفية التعامل مع بعض أمراضها ،مع إمكانية الحجز إلكترونيا, بحيث يقوم المريض باختيار طبيب ثم استعراض مواعيده وحجز الموعد. بالإضافة إلى أن النظام يقوم تلقائياَ بإرسال إشعار للمريض في حال تم إلغاء الموعد أو تغييره من قبل الطبيب. وقد تمت برمجة الموقع باستخدام لغة php واستخدمت كودات النقل STMP للإرسال والإستقبال .
Number of page 62 , تكنولوجيا المعلومات 2/2017
Keywords: عيادات ، العيون ، الالكترونية ، حجز ، ارشاد ، تشخيص